Defining resilience for the US building industry. Issue 4 (19th May 2019) - Kurth, Margaret H.; Keenan, Jesse M.; Sasani, Mehrdad; Linkov, Igor
ABSTRACT: Initiatives to operationalize the concept of resilience in the building industry are rapidly emerging. The concept of resilience has introduced a way to explore solutions to some important problems in the building industry. However, much of the work that has taken place to date represents activities generally assigned to risk management, which is discussed as being inherently insufficient for sustaining the functions of the built environment under stresses. This commentary considers the opportunities and limitations for mainstreaming resilience into building industry processes and actors. Barriers include indeterminate analytical meaning, event and performance uncertainty, immature regulatory standards setting, and untested enterprise economics. Further, the multiple outcomes of recovery and the relationship between building recovery and adaptation are discussed and, along with economics of resilience investments, a research need highlighted. A simple heuristic is presented to illustrate the complement of resilience to risk management and advance the integration of resilience into existing industry workflows.